Emerging Contaminants in Soil and Water - Bayabil, Haimanote K.; Teshome, Fitsum T.; Li, Yuncong C. (Frontiers in Environmental Science, 2022)
The global population increase puts tremendous pressure on the already dwindling natural resources such as soil and freshwater. Healthy and productive soils as well as the availability of freshwater resources are critical for agricultural productivity. On the other hand, climate change and variability make the water scarcity problem even worse. Agriculture, being the biggest consumer of fresh water, is expected to be affected significantly. Yet, agriculture is expected to play a significant role in achieving greater food, and fiber needs to meet the growing global population. In addition, soil and water quality are also becoming a bigger threat to soil productivity and freshwater availability. Some portion of nutrients applied to agriculture and urban landscapes end up in runoff and leaching water that feeds streams, rivers, lakes, groundwater, etc. These excess nutrient loadings are causing soil and water quality deterioration, which could have severe impacts on human health, aquatic ecosystems, and environmental sustainability. In addition to nutrient and chemical pollutions, emerging contaminants such as heavy metals are showing an increasing trend in soil and freshwater bodies. These emerging contaminants not only impair soil quality and freshwater sources but could also get into the food chain and affect human and animal health. While growing evidence is becoming available on the increasing threats from emerging contaminants, research and understanding are still limited. This mini-review paper summarizes available research on types of emerging contaminants and their impacts on soil and water quality.